Ruthenium(II) complexes with hydroxypyridinecarboxylates: screening potential metallodrugs against Mycobacterium tuberculosis - Barbosa, Marilia I. F.; Correa, Rodrigo S.; Pozzi, Lucas V.; Lopes, Erica de O. [UNESP]; Pavan, Fernando R. [UNESP]; Leite, Clarice Q. F. [UNESP]; Ellena, Javier; Machado, Sergio de P.; Von Poelhsitz, Gustavo; Batista, Alzir A. (Elsevier B.V., 2015)
Three promising antimycobacterium tuberculosis ruthenium(II) complexes with the deprotonated ligands 2-hydroxynicotinic acid (2-OHnicH), 6-hydroxynicotinic acid (6-OHnicH) and 3-hydroxypicolinic acid (3-OHpicH) were synthesized and characterized. Structural analysis revealed three different coordination modes depending of the hydroxypyridinecarboxylate ligand. In the complex [Ru(2-OHnic)(dppb)(bipy)PF6 (1), the 2-OHnic anion is coordinated by the O,O-chelating mode (via carboxylate group and phenolate oxygen), in the Ru(6-OHnic)(dppb)(bipy)]PF6 (2) a O-O chelation by the carboxylate group is observed for the 6-OHnic ligand and for the complex [Ru(3-OHpic)(dppb)(bipy))PF6 (3) a N,O-chelating mode (via carboxylate) occurs to the 3-OHpic anion. The compounds were evaluated for activity against Mycobacterium tuberculosis H(37)Rv ATCC 27294 using Resazurin Microtitre Assay (REMA) plate method and cytotoxicity in VERO CCL-81 cell line. All the synthesized compounds exhibited good antimycobacterial activity and a completely lack of cytotoxicity activity, indicating a good selectivity index. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Mycobacterium tuberculosis; Cytotoxicity; Ruthenium(II) complexes; Metallodrugs; Hydroxypyridinecarboxylates